Ulah Pati di Bali dalam Perspektif Sosiologi Hindu - Wardana Yasa , I Ketut; Adisastra, I Nyoman Surpa (Jurnal Penelitian Agama Hindu, 2025)
Suicide (Ulah pati) is a global public health problem, including in Bali. Bali faces a serious problem related to its high suicide rate, even being recorded as the region with the highest percentage of suicide cases in Indonesia in 2024. This study aims to examine in-depth the issue of suicide in Bali, the Hindu perspective, and to identify potential steps that can be taken from the perspective of Hindu Sociology. This research is a qualitative study with a literature review. The data were analyzed and presented in a descriptive form. The research findings indicate that Balinese society is fundamentally shaped by deeply rooted cultural and religious values, yet potential psychological vulnerabilities may occur in individuals triggered by internal and external factors of the perpetrators who are also the victims of suicide. The general view of Hinduism opposes suicide, although there are exceptions or more lenient interpretations under certain conditions, including Sati, Prayopavesa, and self-sacrifice in emergencies. As Durkheim argues, the suicide rate is a social fact, not merely an individual one, which means that suicide is influenced by other social facts, so the prevention of Ulah pati requires a holistic effort from all elements, including individuals, families, and the community.